Understanding Tourist Brand Loyalty: Key Antecedents in Annapurna Region's Resorts in Nepal - Shrestha, Sajeeb Kumar; Thapa, Ganga; Karki, Tej Bahadur; Shrestha, Hira Lal; Neupane, Dasarath (Nepal Journal of Multidisciplinary Research, 2025)
Background: Brand loyalty in tourism sector is frequently talked but it does not appear to have been researched in an authentic manner. This study tries to uncover the facts in the context of perceived facilities, service quality and price value in Annapurna Region's Resorts in Nepal. This present article attempts to measure the brand loyalty of foreign tourist in the resorts located at the Annapurna Region. Methods: Descriptive and causal research design was used as it is quantitative in nature. Structured questionnaires were administered in the survey. Two hundred and fifty tourists who stayed in the Annapurna Region's Resorts were approached and data were obtained. Structure equation modelling technique was used to examine the major factors affecting brand loyalty in the resorts located at the Annapurna Region. Results: This research confirmed perceived facilities and service quality were the most important factors on brand loyalty. Price value has no significant effect on brand loyalty for tourists located in Annapurna Region's Resorts. Conclusion: Marketing managers should concentrate on service quality provided in the resorts at Annapurna Region and tries to know how it is perceived by tourists.